PENGARUH KEPEMIMPINAN, PROMOSI JABATAN, TERHADAP KINERJA PEGAWAI, DAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PD PASAR JAYA - Guston Sitorus (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2016)
The objective of this research is to analize and test the effect of leadership, job promotion, and job satisfaction on performance. Performance is assumed to be significantly effected by the leadership, job promotion, and job satisfaction that pertain in the organization. The causal study reported here aimed to examine the hypothesis. It was conducted through a survey in the PD Pasar Jaya a sample of 90 people randomly selected from the overall population of 135 employe. The data of each variable were collected separately by the respondens’ filling in a questionnaire. The path technique was applied to analyze the data wich had been previously treated with the aggressive and coorelation procedure. The result proved that the employee performance was directly effected by the leadership, the jo promotion and the job satisfaction, and job satisfaction was in turn, directly effected by leadership and job promotion. The findings suggest that the variation of performance of the employee might have been effected by the leadership, the job promotion, and the job satisfaction in the organization. This further implies the need take the variables of leadership, job satisfaction, and performance into the consideration in the strategic planning of the human resources development in the PD Pasar Jaya